Population Growth of the Cladoceran, Daphnia magna: A Quantitative Analysis of the Effects of Different Algal Food - Choi, Jong-Yun (Public Library of Science, 2014)
In this study, we examined the effects of two phytoplankton species, Chlorella vulgaris and Stephanodiscus hantzschii, on growth of the zooplankton Daphnia magna. Our experimental approach utilized stable isotopes to determine the contribution of food algae to offspring characteristics and to the size of adult D. magna individuals. When equal amounts of food algae were provided (in terms of carbon content), the size of individuals, adult zooplankton, and their offspring increased significantly following the provision of S. hantzschii, but not after the provision of C. vulgaris or of a combination of the two species. Offspring size was unaffected when C. vulgaris or a mixture of the two algal species was delivered, whereas providing only S. hantzschii increased the production of larger-sized offspring. Stable isotope analysis revealed significant assimilation of diatom-derived materials that was important for the growth of D. magna populations. Our results confirm the applicability of stable isotope approaches for clarifying the contribution of different food algae and elucidate the importance of food quality for growth of D. magna individuals and populations. Furthermore, we expect that stable isotope analysis will help to further precisely examine the contribution of prey to predators or grazers in controlled experiments.